2017
DOI: 10.5898/jhri.6.3.short
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Agency in Interactions Between ChildrenWith Autism and Socially Assistive Robots

Abstract: Socially assistive robotics (SAR) has increasingly been shown to have potential as a tool for social skills therapy for children with autism, a developmental disorder associated with atypical social development. This work presents the results of a study of robot agency on child-robot interactions involving children with autism. We describe the development of a SAR interaction scenario with both agent-like and object-like robot behaviors and present the results of a pilot study of six children with autism inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 53 publications
2
11
0
1
Order By: Relevance
“…In our study, we observed that six children did not engage with the robot or learning task. Similar to other studies that report aversive reactions of autistic children toward robots (e.g., Bekele et al, 2014 ; Short et al, 2017 ), we also observed aversive reactions of two of the six children. For one child, it was the first session with the robot.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, we observed that six children did not engage with the robot or learning task. Similar to other studies that report aversive reactions of autistic children toward robots (e.g., Bekele et al, 2014 ; Short et al, 2017 ), we also observed aversive reactions of two of the six children. For one child, it was the first session with the robot.…”
Section: Discussionsupporting
confidence: 91%
“…As a result, there are large individual differences in how autistic children interact with a robot. While the cognitive processes underlying the perception of robots by autistic children remains unclear, there is behavioral evidence of autistic children interacting with robots in object-like manners, as well as interactions where they may consider the robot a social actor (Short et al, 2017 ). Moreover, compared to typically developing children who readily attribute human-like characteristics to a robot (Beran et al, 2011 ), there is preliminary evidence for autistic users, where this tendency was found to be reduced for autistic children (Chaminade et al, 2015 ) as well as autistic adults (Bird et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…In areas such as elderly care, behavioural therapy, mental health care, dementia care, rehabilitation, and education, people increasingly interact with robots, who encourage them to do their own work. For example, robots ('Chili') have been used in experiments to teach and motivate first-graders to make healthy food choices (Short et al 2017). This is essentially a coproduction process.…”
Section: Motivationmentioning
confidence: 99%
“…As humans establish emotional ties with whom they interact, this fact may remain the same for a human-robot interaction as well. Hence, the proactive, social means of engagement are expected from a robot in such a scenario [ 15 ]. One aspect in developing mechanisms to enhance social intelligence in robots is to improve the user experience with such robots.…”
Section: Introductionmentioning
confidence: 99%